THE ROLE OF INTERACTIVE METHODS IN TEACHING ENGLISH LANGUAGE. (Ustozlar uchun, 2025)
This article examines effective methods of teaching English in preschool education. The study highlights the importance of early language exposure, age-appropriate teaching strategies, and interactive activities in developing basic English language skills among preschool children. The research analyzes modern pedagogical approaches, including play-based learning, visual aids, songs, and storytelling, and evaluates their impact on children’s motivation and language acquisition. The results show that innovative and child-centered methods significantly improve vocabulary development, listening skills, and positive attitudes toward learning English.